Risks to human and animal health related to the presence of moniliformin in food and feed. (2nd March 2018) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Hoogenboom, Laurentius (Ron); et al.
Abstract: Moniliformin (MON) is a mycotoxin with low molecular weight primarily produced by Fusarium fungi and occurring predominantly in cereal grains. Following a request of the European Commission, the CONTAM Panel assessed the risk of MON to human and animal health related to its presence in food and feed. The limited information available on toxicity and on toxicokinetics in experimental and farm animals indicated haematotoxicity and cardiotoxicity as major adverse health effects of MON. MON causes chromosome aberrations in vitro but no in vivo genotoxicity data and no carcinogenicity data were identified. Due to the limitations in the available toxicity data, human acute or chronic health‐based guidance values (HBGV) could not be established. The margin of exposure (MOE) between the no‐observed‐adverse‐effect level (NOAEL) of 6.0 mg/kg body weight (bw) for cardiotoxicity from a subacute study in rats and the acute upper bound (UB) dietary exposure estimates ranged between 4, 000 and 73, 000. The MOE between the lowest benchmark dose lower confidence limit (for a 5% response ‐ BMDL05 ) of 0.20 mg MON/kg bw per day for haematological hazards from a 28‐day study in pigs and the chronic dietary human exposure estimates ranged between 370 and 5, 000, 000 for chronic dietary exposures. These MOEs indicate a low risk for human health but were associated with high uncertainty. The toxicity data available for poultry, pigs, and mink indicated a low or even negligible risk for these animals from exposure to MON in feed at the estimated exposure levels under current feeding practices. Assuming similar or lower sensitivity as for pigs, the CONTAM Panel considered a low or even negligible risk for the other animal species for which no toxicity data suitable for hazard characterisation were identified. Additional toxicity studies are needed and depending on their outcome, the collection of more occurrence data on MON in food and feed is recommended to enable a comprehensive human risk assessment.